Living standards, poverty and inequality in the UK: 2017 - Jonathan Cribb; Andrew Hood; Robert Joyce; Agnes Norris Keiller (Institute for Fiscal Studies (IFS), 2017)
This report examines changes in the distribution of household incomes in the UK, and the determinants and consequences of recent trends. This includes analysing not only changes in average living standards, but also inequality in household incomes and measures of income poverty and deprivation. We put these into historical context using comparable data spanning the last 50 years. The analysis is based on data from two main UK household surveys. The first is the Family Resources Survey (FRS), a survey of more than 20,000 households a year, which contains detailed information on different sources of household incomes. We use household income variables derived from the FRS by the UK government's Department for Work and Pensions (DWP). These measures of incomes underlie the DWP's annual statistics on the distribution of income, known as "Households Below Average Income" (HBAI). In addition, we use information from Understanding Society. This is a longitudinal survey that follows the same people from one wave to the next, which allows us to examine changes in individual households' incomes and economic circumstances ...
Keywords: 330